The Effect of Fu's Subcutaneous Needling Combined with Reperfusion Approach on Surface Electromyography Signals in Patients with Cervical Spondylosis and Neck Pain: A Clinical Trial Protocol. (22nd September 2022) - Peng, Junliang; Yang, Jiaen; Feng, Jiaqi; Zhou, Guangjin; Dong, Li; Lin, Rong; Wang, Dong
Abstract : Background . Neck pain is one of the most common musculoskeletal diseases. Fu's subcutaneous needling therapy is a special acupuncture method that targets muscle trigger points. It has been proven to have a positive effect on the treatment of neck pain. The access to its curative effect may be related to the improvement of muscle and soft tissue condition. The purpose of this study is to evaluate the outcome of Fu's subcutaneous needling therapy for patients with neck pain by collecting changes in the sEMG of the patient's neck muscles and related data from evaluation scales and explore the feasibility and safety of Fu's subcutaneous needling therapy for neck pain. Methods . 72 patients meeting the inclusion criteria were randomly divided into FSN group and acupuncture group for corresponding treatment. FSN group was treated once every other day for 5 consecutive treatments; the acupuncture group was treated once a day for 10 consecutive treatments. Result . Outcome indicators were measured at baseline, after the first treatment and the end of the treatment. Primary outcome indicators: average EMG (AEMG) and (mean power frequency) MPF of sternocleidomastoid muscle and superior trapezius muscle. Secondary outcome indicators: Mc Gill pain questionnaire (MPQ), neck disability index (NDI), and adverse reactions. Conclusions . This study will explore the efficacy, safety, and possible mechanism of Fu's subcutaneous needling therapy for patients with neck pain, thus to provide more evidence support for clinical decision-making. This trial is registered with Chinese Clinical Trial Register Center (registration number ChiCTR2100043529 ).